Terapi Zikir Jama’ati di Desa Luwoo dan Tenggela Kabupaten Gorontalo - Aris Saefulloh (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
Jama’ati Muslim group of Luwoo and Tenggela villages in Gorontalo regency is one of the groups that routinely remembrance activities in their environment. By using psychological, this paper will attempt to explore the existence and the implementation of remembrance